CO2 EMISSIONS AND HEAT FLOW THROUGH SOIL, FUMAROLES, AND STEAM HEATED MUD POOLS AT THE REYKJANES GEOTHERMAL AREA, SW ICELAND - Fridriksson T.; Kristjánsson B.R.; Ármannsson H.; Margrétardóttir E.; Ólafsdóttir S.; Chiodini G. (My University, 2006)
Carbon dioxide emissions and heat flow through soil, steam vents and fractures, and steam heated mud pools were determined in the Reykjanes geothermal area, SW Iceland. Soil diffuse degassing of CO2 was quantified by soil flux measurements on a 600 m by 375 m rectangular grid using a portable closed chamber soil flux meter and the resulting data were analyzed by both a graphical statistical method and sequential Gaussian simulations. The soil temperature was measured in each node of the grid and used to evaluate the heat flow. The heat flow data were also analyzed by sequential Gaussian simulations. Heat flow from steam vents and fractures was determined by quantifying the amount of steam emitted from the vents by direct measurements of steam flow rate. The heat loss from the steam heated mud pools was determined by quantifying the rate of heat loss from the pools by evaporation, convection, and radiation. The steam flow rate into the pools was calculated from the observed heat loss from the pools, assuming that steam flow was the only mechanism of heat transport into the pool. The CO2 emissions from the steam vents and mud pools were determined by multiplying the steam flow rate from the respective sources by the representative CO2 concentration of steam in the Reykjanes area. The observed rates of CO2 emissions through soil, steam vents, and steam heated mud pools amounted to 13.5 ± 1.7, 0.23 ± 0.05, and 0.13 ± 0.03 tons per day, respectively. The heat flow through soil, steam vents, and mud pools was 16.9 ± 1.4, 2.2 ± 0.4, and 1.2 ± 0.1 MW, respectively. Heat loss from the geothermal reservoir, inferred from the CO2 emissions through the soil amounts to 130 ± 16 MW of thermal energy. The discrepancy between the observed heat loss and the heat loss inferred from the CO2 emissions is attributed to steam condensation in the subsurface due to interactions with cold ground water. These results demonstrate that soil diffuse degassing can be a more reliable proxy for heat loss from geothermal systems than soil temperatures. The soil diffuse degassing at Reykjanes appears to be strongly controlled by the local tectonics. The observed diffuse degassing defines 3-5 elongated N-S trending zones (000-020°). The orientation of the diffuse degassing structures at Reykjanes is consistent with reported trends of right lateral strike slip faults in the area. The natural CO2 emissions from Reykjanes under the current low-production conditions are about 16% of the expected emissions from a 100 MWe power plant, which has recently been commissioned at Reykjanes. © 2006 Elsevier Ltd. All rights reserved.